ADAPTIVE NEURO-FUZZY INFERENCE SYSTEM FOR COMPUTING THE RESONANT FREQUENCY OF CIRCULAR MICROSTRIP ANTENNAS - Guney, Kerim; Sarikaya, Nurcan (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A new method for computing the resonant frequency of the circular microstrip antenna, based on the adaptive neuro-fuzzy inference system (ANFIS), is presented. A hybrid learning algorithm is used to identify the parameters of ANFIS. The results of the new method are in excellent agreement with the experimental results reported elsewhere.